Recommendations for improving access to healthcare for street-connected children and youth in Kenya: A qualitative study. (December 2021) - Embleton, L.; Shah, P.; Gayapersad, A.; Kiptui, R.; Ayuku, D.; Wachira, J.; Apondi, E.; Braitstein, P.
Highlights: SCY require access to healthcare that is responsive to their lives on the street. SCY require universal health coverage to alleviate economic barriers to care. Healthcare providers need to be trained and sensitized to provide care to SCY. Multidisciplinary and holistic approaches to healthcare for SCY are essential. Abstract: Background: Street-connected children and youth (SCY) in Kenya have a high burden of disease and require access to healthcare that is responsive and sensitive to their needs and situation living and working on the streets. However, evidence suggests that SCY in Kenya are facing significant barriers to accessing healthcare, which may be impacting their health and well-being. Therefore, we sought to identify opportunities for ameliorating access to healthcare for SCY in Kenya from stakeholders including healthcare providers, SCY, policymakers, and community members. Methods: This qualitative analysis focuses on a sub-set of data concerning the delivery of healthcare to SCY and recommendations to improve access to healthcare for this population. We interviewed 100 participants in focus group discussions and in-depth interviews across 5 counties in Kenya from May 2017 and September 2018. We conducted a thematic analysis situated in a conceptual framework for access to healthcare. Our results are presented in five major themes positioned in this conceptual framework's five dimensions of accessibility of care and five corresponding abilities of persons: approachability and ability to perceive the need for healthcare; acceptability of health services and ability to seek healthcare; availability and accommodation of health services and ability to reach healthcare; affordability and ability to pay for healthcare services; appropriateness of care and ability to engage as an empowered patient with the health system. Results: Our results found three fundamental components of ameliorating access to healthcare for SCY in Kenya including: 1) the need for universal health coverage for SCY to alleviate barriers with respect to affordability, ability to pay, availability, and ability to reach; 2) the need to ensure that healthcare providers are trained and sensitized to provide care to SCY to improve acceptability; and 3) that multidisciplinary, holistic, and community-based approaches to healthcare for SCY are essential in order to adequately meet their distinct needs. Conclusion: SCY in Kenya urgently require access to quality healthcare given their substantial morbidities and mortality. Improving access to healthcare for SCY requires addressing a lack of affordability and an inability to pay. It also requires healthcare providers to feel supported and resourced to provide care to SCY to resolve issues of acceptability. Finally, given SCY's multitude of unmet needs, multidisciplinary and community-based approaches to care may be integral to improving short- and long-term health and well-being for SCY.